2019
DOI: 10.5194/essd-11-409-2019
|View full text |Cite
|
Sign up to set email alerts
|

Historical and recent aufeis in the Indigirka River basin (Russia)

Abstract: Abstract. A detailed spatial geodatabase of aufeis (or naled in Russian) within the Indigirka River watershed (305 000 km2), Russia, was compiled from historical Russian publications (year 1958), topographic maps (years 1970–1980s) and Landsat images (year 2013–2017). Identification of aufeis by late spring Landsat images was performed with a semi-automated approach according to Normalized Difference Snow Index (NDSI) and additional data. After this, a cross-reference index was set for each aufeis field to lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The assessment of aufeis area conducted for the Indigirka River basin based on recent Landsat imagery analysis has shown that the number of aufeis fields increased by 35 %, but the total area decreased by 1.6 times (Makarieva et al, 2019a) in comparison with the data by Simakov and Shilnikovskaya (1958). The current aufeis area share for the studied watersheds in the Indigirka River basin ranges from 0.26 % to 0.80 % (Makarieva et al, 2019a), though historical estimations are higher. For example, Tolstikhin (1974) estimates that relative aufeis area averages 0.4 % to 1.3 %, reaching 4 % in the basins of some rivers.…”
Section: Glaciers Rock Glaciers and Aufeismentioning
confidence: 78%
See 1 more Smart Citation
“…The assessment of aufeis area conducted for the Indigirka River basin based on recent Landsat imagery analysis has shown that the number of aufeis fields increased by 35 %, but the total area decreased by 1.6 times (Makarieva et al, 2019a) in comparison with the data by Simakov and Shilnikovskaya (1958). The current aufeis area share for the studied watersheds in the Indigirka River basin ranges from 0.26 % to 0.80 % (Makarieva et al, 2019a), though historical estimations are higher. For example, Tolstikhin (1974) estimates that relative aufeis area averages 0.4 % to 1.3 %, reaching 4 % in the basins of some rivers.…”
Section: Glaciers Rock Glaciers and Aufeismentioning
confidence: 78%
“…Approximately 85 % of the total terrestrial runoff to the Arctic Ocean is supplied by rivers draining from Russia (Aagaard and Carmack, 1989). Moreover, Makarieva et al (2019b) have shown that most runoff of the Indigirka River is generated in mountainous areas and not from the coastal plains. Therefore, the analysis of this database, including the mountainous upstreams of the Yana and Indigirka rivers, is particularly timely.…”
Section: Overall Impacts To the Ecosystemmentioning
confidence: 99%
“…The aufeis accumulates 26 km 3 of ground water in the free water exchange zone (36 % of their total dynamic reserves). The total volume of aufeis is about 30 km 3 , which corresponds to 25 mm of water layer at the area of 1.2 million km 2 [5]. Aufeis is the climate regulator of underground and river flow.…”
Section: Aufeis-taryns Of the North-east Of Russiamentioning
confidence: 99%
“…The developed Catalogue contains the coordinates and characteristics of 896 aufeis with a total area of 2064 km 2 in the Indigirka River basin [3,10], 385 aufeis with a total area of 738 km 2 in the Yana River basin, 1765 aufeis with a total area of 1945 km 2 in the Kolyma River basin, and 1599 aufeis with a total area of 2434 km 2 in Chukotka (Fig. 2).…”
Section: Catalogue Of Aufeis Of the North-east Of Russiamentioning
confidence: 99%
See 1 more Smart Citation